PENDAMPINGAN KONDISI FISIK CABANG OLAHRAGA BULUTANGKIS MENGGUNAKAN LATIHAN LADDER DRILL RESISTANCE BAND - Soemardiawan, Soemardiawan; Supriyatnak, Kokom; Anggraini, Fitri; Gunawan, I Made Sony; Marzuki, Ismail; Yundarwati, Susi (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
This research was motivated by the lack of agility among badminton athletes, especially when defending and attacking in the front, side, and back areas of the court, which often results in losing the shuttlecock. To address this issue, physical conditioning training was conducted using a combination of ladder drills and resistance band training. Ladder drills are a form of jumping exercise with one or two feet across a ladder-shaped rope placed on the floor or ground. Resistance bands are elastic bands used in strength and flexibility training. This training method is divided into two main stages. The first stage includes providing theoretical knowledge and discussion, material delivery, program design, and evaluation. In this stage, participants will receive an in-depth explanation of correct badminton techniques and specific training programs related to physical conditioning training using ladder drills and resistance bands. The second stage is the implementation of physical training practices. This training was conducted by lecturers from the Sports and Health Education Study Program, Faculty of Sport Science and Public Health, Mandalika University of Education on June 3-4, 2025, at the badminton court of the Warna Agung Sports Hall. ABSTRAK Penelitian ini dilatarbelakangi oleh masih kurangnya kelincahan atlet bulu tangkis, terutama saat bertahan dan menyerang di area depan, samping, dan belakang lapangan, yang sering mengakibatkan kehilangan shuttlecock. Untuk mengatasi masalah tersebut, dilakukan pendampingan kondisi fisik menggunakan kombinasi latihan ladder drill dan resistance band. Ladder drill sendiri merupakan bentuk latihan melompat dengan satu atau dua kaki melintasi tali berbentuk tangga yang diletakkan di lantai atau tanah. Resintance band adalah pita elastis yang digunakan dalam latihan kekuatan dan fleksibilitas. Metode pendampingan ini terbagi menjadi dua tahap utama. Tahap pertama meliputi pemberian pengetahuan teori dan diskusi, penyampaian materi, perancangan program, serta evaluasi. Pada tahap ini, peserta akan mendapatkan penjelasan mendalam mengenai teknik bulu tangkis yang benar dan program latihan spesifik yang berkaitan dengan pendampingan kondisi fisik menggunakan ladder drill dan resistance band. Tahap kedua adalah pelaksanaan praktik latihan fisik. Pelatihan ini dilaksanakan oleh dosen Program Studi Pendidikan Olahraga dan Kesehatan Fakultas Ilmu Keolahragaan dan Kesehatan Masyarakat Universitas Pendidikan Mandalika pada tanggal 3-4 Juni 2025 di lapangan bulu tangkis Gor Warna Agung.